RISK FACTORS FOR OVERWEIGHT AND OBESITY AMONG TODDLERS IN A COASTAL AREA OF INDONESIA: A CASE-CONTROL STUDY - Agung Wicaksono; Apoina Kartini; Siti Fatimah (International Archives of Medical Sciences and Public Health, 2026)
Overweight and obesity among toddlers have emerged as important public health concerns in Indonesia, particularly in coastal areas where dietary patterns and socioeconomic conditions may increase nutritional risk. However, evidence on their determinants in these settings remains limited. This study aimed to identify factors associated with overweight and obesity among toddlers aged 13–60 months in the working area of Puskesmas Munjungan, Trenggalek Regency. A case-control study was conducted involving 136 toddlers, consisting of overweight/obese cases and normal-weight controls selected through proportionate stratified random sampling. Data on dietary intake, early feeding practices, and maternal characteristics were collected using questionnaires and anthropometric assessment. Data were analyzed using Chi-square tests and multiple logistic regression. Backward stepwise selection was applied for exploratory model building, although its limitations related to variable retention stability were acknowledged. The results indicated that nutritional intake, early feeding practices, and maternal characteristics were significantly associated with overweight and obesity among toddlers. Multivariate analysis identified non-exclusive breastfeeding as the factor most strongly associated with overweight and obesity, followed by high energy and macronutrient intake, poor maternal nutritional knowledge, and higher maternal body mass index. Given the retrospective assessment of dietary exposure and feeding history, the possibility of reverse causation cannot be excluded; therefore, these findings should be interpreted as statistical associations rather than evidence of causal relationships. In conclusion, overweight and obesity among toddlers in coastal areas were associated with modifiable nutritional and maternal factors, with early feeding practices showing the strongest association. Strengthening exclusive breastfeeding promotion, improving maternal nutritional knowledge, and encouraging balanced dietary practices may support prevention efforts in coastal communities.